2011
DOI: 10.1152/ajplung.00422.2010
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin regulates CXC chemokine formation in streptococcal M1 protein-induced neutrophil infiltration in the lung

Abstract: Streptococcus pyogenes of the M1 serotype can cause streptococcal toxic shock syndrome and acute lung injury. Statins exert beneficial effects in septic patients although the mechanisms remain elusive. This study examined effects of simvastatin on M1 protein-provoked pulmonary inflammation and tissue injury. Male C57BL/6 mice were pretreated with simvastatin or a CXCR2 antagonist before M1 protein challenge. Bronchoalveolar fluid and lung tissue were harvested for determination of neutrophil infiltration, form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 63 publications
4
33
0
1
Order By: Relevance
“…In addition to the anti-viral effects of simvastatin demonstrated in this study, there are other reports indicating that simvastatin has antimicrobial activity. For example, simvastatin is protective during Staphylococcus aureus pneumonia [21] and ameliorates acute lung injury in streptococcal infections [22]. A recent study indicates that oral simvastatin at physiologically relevant doses only modestly protects against pneumococcal pneumonia [23].…”
Section: Pulmonary Infections Cs Lee Et Almentioning
confidence: 99%
“…In addition to the anti-viral effects of simvastatin demonstrated in this study, there are other reports indicating that simvastatin has antimicrobial activity. For example, simvastatin is protective during Staphylococcus aureus pneumonia [21] and ameliorates acute lung injury in streptococcal infections [22]. A recent study indicates that oral simvastatin at physiologically relevant doses only modestly protects against pneumococcal pneumonia [23].…”
Section: Pulmonary Infections Cs Lee Et Almentioning
confidence: 99%
“…Tissue myeloperoxidase (MPO) activity is a quantitative marker for the presence of neutrophils in the lungs (55). MPO activity was measured in tissue homogenates at 24 h after LPS injection in placebo and dopamine treated animals (n ϭ 6).…”
Section: Biochemical Assaysmentioning
confidence: 99%
“…A functional role of CXC chemokines has been proposed in streptococcal infections (44), and we have demonstrated that M1 protein is a potent stimulator of CXCL1 and CXCL2 production in the lung (41). Herein, we found that inhibition of CD162 reduced M1 protein-induced formation of CXCL1 and CXCL2 in the lung.…”
Section: Discussionmentioning
confidence: 58%
“…A recent study demonstrated that M1 proteinprovoked pulmonary accumulation of neutrophils is critically dependent on the synthesis and action of CXC chemokines (44). Thus, the chemokine-mediated mechanisms behind accumulation of neutrophils in the lung are relatively well known, whereas the adhesive mechanisms regulating M1 protein-induced neutrophil recruitment and tissue damage in the lung remain elusive.…”
mentioning
confidence: 99%